2023
DOI: 10.3390/brainsci13071097
|View full text |Cite
|
Sign up to set email alerts
|

Higher Serum E-Selectin Levels Associated with Malignant Brain Edema after Endovascular Thrombectomy for Ischemic Stroke: A Pilot Study

Abstract: Background and Purpose: Little is known about the effect of soluble adhesion molecules on malignant brain edema (MBE) after endovascular thrombectomy (EVT). This study aimed to explore the association between serum concentrations of E-selectin and the risk of MBE in patients who received EVT. Methods: Patients with a large vessel occlusion stroke in the anterior circulation who underwent EVT were prospectively recruited. Serum soluble E-selectin concentrations were measured after admission for all patients. MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Higher levels of selectins have been associated with exacerbated post-stroke inflammation, BBB disruption, and potential complications like HT and brain edema ( Jin et al, 2011 ; Hase et al, 2012 ; Salas-Perdomo et al, 2018 ; Li et al, 2020 ). Recently a prospective study demonstrated that higher serum E-selectin levels were statistically significantly associated with an increased risk of malignant brain edema in ischemic stroke patients receiving endovascular thrombectomy treatment ( Hu et al, 2022 ; Zhou et al, 2023 ).…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Higher levels of selectins have been associated with exacerbated post-stroke inflammation, BBB disruption, and potential complications like HT and brain edema ( Jin et al, 2011 ; Hase et al, 2012 ; Salas-Perdomo et al, 2018 ; Li et al, 2020 ). Recently a prospective study demonstrated that higher serum E-selectin levels were statistically significantly associated with an increased risk of malignant brain edema in ischemic stroke patients receiving endovascular thrombectomy treatment ( Hu et al, 2022 ; Zhou et al, 2023 ).…”
Section: Inflammatory Markersmentioning
confidence: 99%